The ecological and economic values of a 50 years old secondary forest in East Kalimantan, Indonesia - Karmini Karmini; Karyati Karyati; Kusno Yuli Widiati (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Karmini, Karyati, Widiati KY. 2021. The ecological and economic values of a 50 years old secondary forest in East Kalimantan, Indonesia. Biodiversitas 22: 4597-4607. Secondary forests in the tropics are often ignored since they are assumed to have low ecological functions while on the other hand the economic values have been reduced. This study aimed to analyze the ecological and economic values of a 50-year secondary forest in East Kalimantan that experienced several various land-use changes. The ecological aspects analyzed were stand structure, floristic composition, and species diversity. Economic aspects include log prices, logging costs, profit margins, and stumpage values. A vegetation survey of woody trees with a diameter at breast height of more than 5 cm was carried out on ten plots measuring 20 m × 20 m each. A total of 437 trees belonging to 38 species, 30 genera, and 19 families were recorded with Moraceae and Euphorbiaceae were the most dominant families with Family Important Value (FIV) of 86.79. The three most dominant species were Macaranga motleyana (IVi of 50.95), Artocarpus elasticus (IVi of 34.41), and Symplocos fasciculata (IVi of 31.46). The trees in the study plot have a diversity index of 1.33, dominance index of 0.07, evenness index of 0.37, and species richness of 6.09. The average logging cost, logs price, lumber price, profit margin, and stumpage value at secondary forest were USD69.43 m-3, USD44.63 m-3, USD100.03 m-3, USD10.30 m-3, and USD28.73 ha-1, respectively. The 50 years old secondary forests in East Kalimantan have biodiversity, especially trees that have economic value, therefore their existence needs to be preserved and their use is carried out by maintaining and increasing biodiversity.